Thorough Characterization of Brazilian New Generation of Eucalypt Clones and Grass for Pulp Production. (23rd February 2015) - Gomes, Fernando José Borges; Colodette, Jorge Luiz; Burnet, Auphélia; Batalha, Larisse Aparecida Ribas; Santos, Fernando Almeida; Demuner, Iara Fontes
Abstract : Eucalypt wood is becoming the most important raw material for the pulp industries in South America. However, due to the high wood cost in comparison to other raw material sources, nonwoody materials are also being investigated aiming at pulp production. In this way, this paper aimed at the evaluation of eighteen eucalypt clones obtained from the Brazilian Genolyptus project, regarding their potential characteristics for pulp production. Aiming at the same goal, two species of elephant grass were also evaluated as alternative raw material sources. Through the analyses of the anatomic and chemical characteristics, five eucalypt clones and one elephant grass species were indicated for pulp production and biorefinery application. The results of this study indicate the high technological quality of Eucalyptus clones evaluated and indicate that they can be used for biorefinery applications since they have the suitable characteristics. In general, the eucalypt clones are less moist and denser and contain fewer minerals and extraneous materials than the elephant grass species, which make them more attractive for utilization in deconstruction studies aiming at production of bioproducts.